Decompression Versus Fusion for Grade I Degenerative Spondylolisthesis: A Meta-Analysis. Issue 2 (April 2019) - Koenig, Scott; Jauregui, Julio J.; Shasti, Mark; Jazini, Ehsan; Koh, Eugene Y.; Banagan, Kelley E.; Gelb, Daniel E.; Ludwig, Steven C.
Study Design: Meta-analysis of evidence level I to IV studies. Objective: To compare decompression alone versus decompression plus fusion in the treatment of grade I degenerative spondylolisthesis (DS). Methods: Following established guidelines, we systematically reviewed 3 electronic databases to assess studies evaluating patients with grade I DS. We stratified all patients into 2 cohorts; the first cohort underwent a decompression-type surgery, and the second cohort underwent decompression plus fusion. We noted clinical outcomes, complications, reoperations, and surgical details such as blood loss. Descriptive statistics and random-effects models were used to determine the specified outcome metrics with 95% confidence intervals (CIs). Results: In both cohorts, the pain (legs and lower back) significantly decreased and the physical component of the Short Form 36 showed better patient clinical outcomes. The decompression cohort had a 5.8% complication rate (95% CI = 1.7-2.1), and the decompression plus fusion cohort had an 8.3% complication rate (95% CI = 5.5-11.6). The reoperation rate was higher in the decompression-only cohort (8.5%; 95% CI = 2.9-17.0) compared with the decompression plus fusion cohort (4.9%; 95% CI = 2.5-7.9). Conclusions: There does not appear to be any advantage of one procedure over the other. Patients undergoing decompression alone tended to be older with a higher percentage of leg pain, whereas patients additionally undergoing fusion tended to be younger with more lower back pain. The decompression-only cohort had fewer complications but a higher revision rate.